2008
DOI: 10.1093/schbul/sbm141
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Ghrelin Levels in Patients With Schizophrenia During Different Antipsychotics Treatment: A Review

Abstract: Energy homeostasis is achieved by the integration of peripheral metabolic signals by the neural circuits involving specific hypothalamic nuclei and brain stem regions. These neural circuits mediate many of the effects of the adipocyte-derived hormone leptin and gut-derived hormone ghrelin. The former is strongly anorexigenic while the latter is the only orexigenic agent active when administered by a peripheral route. Abnormal regulation of these 2 antagonistic regulatory peptides in patients with schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 62 publications
6
85
0
1
Order By: Relevance
“…Ghrelin is a metabolic peptide associated with the regulation of appetite and food intake; ghrelin levels in the brain have been found to change with atypical antipsychotic treatment (82). Interestingly, several lines of evidence have linked ghrelin to WM function (83).…”
Section: Resultsmentioning
confidence: 99%
“…Ghrelin is a metabolic peptide associated with the regulation of appetite and food intake; ghrelin levels in the brain have been found to change with atypical antipsychotic treatment (82). Interestingly, several lines of evidence have linked ghrelin to WM function (83).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have suggested controversial results of the effect of SGAs on circulating ghrelin levels (Sentissi et al, 2008;Jin et al, 2008). One earlier review paper suggested a bi-phasic effect, with downregulated and upregulated ghrelin levels under short-and long-term SGA treatments, respectively (Sentissi et al, 2008).…”
Section: Effects Of Sgas On the Ghrelin Signalling Systemmentioning
confidence: 99%
“…One earlier review paper suggested a bi-phasic effect, with downregulated and upregulated ghrelin levels under short-and long-term SGA treatments, respectively (Sentissi et al, 2008). Another review paper has proposed preliminary explanation suggesting that the negative feedback effect of ghrelin secretion is disrupted under SGA treatments in the long-term (Jin et al, 2008).…”
Section: Effects Of Sgas On the Ghrelin Signalling Systemmentioning
confidence: 99%
“…They typically concentrate on i) dysregulation of neuroendocrinological circuits (e.g., hormonal regulation by the hypothalamus; Sharma et al, 2014); ii) dysregulation of peripheral hormones (e.g., leptin and ghrelin) implicated in weight homeostasis and in regulation of glucose (De Hert et al, 2009;Mitchell et al, 2013;Sentissi et al, 2008); and iii) the effect of antipsychotic medication on weight (Bak et al, 2014;Deng et al, 2010;Sharma et al, 2014). All of these factors are important.…”
Section: Outlook: Possible New Therapies For Comorbid Obesitymentioning
confidence: 99%